INFORMATION PANIC: A CASE STUDY ON BOEDI OETOMO IN THE COLONIAL REPORTS 1908 – 1915 AND 1930 - 1935: Array - Jajang Nurjaman (Arsip Nasional Republik Indonesia, 2018)
In the 19th and early 20th century, the Dutch Colonial Government had experienced an endemic that so called “information panic” about the situation in the Dutch East Indies. One of the case of this information panic is the reports about Boedi Oetomo, one of prominent organizations during early 20th century in Dutch East Indies. The Ministries of Colony in the Netherlands gained many reports from the colony about Boedi Oetomo, namely during its crucial period: the early years of its establishment and the decline of it. This paper aims to examine information panic about Boedi Oetomo. Moreover, this paper also examines the subjects that were discussed in the government reports and how the Dutch Parliament and the Minister of Colonies discussed about this organization in the Netherlands.